Systematic approach towards establishing a National Inventory of Dangerous Pathogens - Iris M. Vennis; Diederik A. Bleijs; Sabrina Brizee; Harold H.J.L. Van Den Berg; Evelien Kampert; Saskia A. Rutjes; Mark W. J. Van Passel (Taylor & Francis Group, 2021)
International regulations stipulate that countries need to organize their biosafety and biosecurity systems to minimize the risk of accidental (biosafety) or malicious intentional (biosecurity) release of dangerous pathogens. International Health Regulations (IHR) benchmarks from the WHO state that even for a level of limited capacity countries need to 'Identify and document human and animal health facilities that store/maintain dangerous pathogens and toxins in the relevant sectors and health professionals responsible for them'. This study provides a stepwise, systematic approach and best practices for countries to initiate a national inventory of dangerous pathogens. With a national inventory of dangerous pathogens a country can identify and document information in a dedicated electronic database on institutes that store or maintain dangerous pathogens. The systematic approach for the implementation of a national inventory of dangerous pathogens consists of four stages; identification, preparation, implementation, and maintenance and evaluation. In the identification phase, commitment of the relevant national ministries is to be established, and a responsible government entity needs to be identified. In the preparatory phase, a list of pathogens to be incorporated in the inventory, as well as a list of institutes to include, is to be agreed upon. In the implementation phase, the institutes are contacted, and the collected data is stored safely and securely in a electronical database. Finally, in the maintenance and evaluation phase meaningful insights are derived and reported to the relevant government authorities. Also, preparations for updates and modifications are undertaken, such as modifications of pathogen lists or institute lists. The approach and database, which is available from the authors, have been tested for the implementation of a national inventory of dangerous pathogens in multiple East-African countries. A national inventory of dangerous pathogens helps countries in strengthening national biosafety and biosecurity as well as in their compliance to IHR.